Analisis Keandalan dan Kinerja Pompa Air Kampus Ben Mboy: Studi Kasus dan Rekomendasi - Tnunay, Imanuel Adam; Adiwijaya, Puji Alphatehah Putra Tri Surya; Manesi, Damianus (Universitas Pertahanan RI, 2024)
This study analyzes the reliability and performance of the water pump at Ben Mboy Campus, focusing on identifying issues and causes of failures, and developing improvement recommendations. An efficient water distribution system is crucial for supporting academic and operational activities at the campus. However, the pump used to transfer water from Rotiklot Dam frequently experiences failures, impacting water supply and operational costs. This research employs a descriptive quantitative method, collecting data through observations, interviews, and performance measurements to evaluate the frequency of pump failures in relation to operational time and workload. Regression analysis reveals a positive relationship between operational time and pump failure frequency, with recommendations to enhance maintenance scheduling and workload monitoring to reduce failures and improve system reliability. The research findings are expected to provide data-driven solutions for improving the water distribution system at Ben Mboy Campus and increasing its operational efficiency.